2019
DOI: 10.1371/journal.ppat.1008142
|View full text |Cite
|
Sign up to set email alerts
|

EV71 infection induces neurodegeneration via activating TLR7 signaling and IL-6 production

Abstract: As a neurotropic virus, human Enterovirus 71 (EV71) infection causes hand-foot-and-mouth disease (HFMD) and may develop severe neurological disorders in infants. Toll-like receptor 7 (TLR7) acts as an innate immune receptor and is also a death receptor in the central nervous system (CNS). However, the mechanisms underlying the regulation of TLR7-mediated brain pathogenesis upon EV71 infection remain largely elusive. Here we reveal a novel mechanism by which EV71 infects astrocytes in the brain and induces neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 55 publications
2
50
0
Order By: Relevance
“…EV71 infection predominantly induces type III IFN production in human IECs. EV71 is a highly infectious RNA virus causing epidemics of hand, foot, and mouth disease (HFMD) and neurological diseases through early infection of host intestine (4,32,33). In this study, we attempted to investigate the effect of EV71 on the induction of IFN signaling in intestine epithelial cells (IECs).…”
Section: Resultsmentioning
confidence: 99%
“…EV71 infection predominantly induces type III IFN production in human IECs. EV71 is a highly infectious RNA virus causing epidemics of hand, foot, and mouth disease (HFMD) and neurological diseases through early infection of host intestine (4,32,33). In this study, we attempted to investigate the effect of EV71 on the induction of IFN signaling in intestine epithelial cells (IECs).…”
Section: Resultsmentioning
confidence: 99%
“…Enterovirus 71 (EV71) is a common pathogen of hand, foot, and mouth disease (HFMD) in children, and it is also the most important risk factor for severe cases and deaths [ 1 4 ].Some children with HFMD can have severe neurological effects, such as aseptic meningitis, encephalitis and acute delayed paralysis, develop serious brainstem encephalitis, neurogenic pulmonary oedema and even die [ 5 , 6 ]. Children with severe neurological diseases who survive often have irreversible sequelae, seriously threatening their health [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, it was demonstrated that HFMD patients with EV-A71 and CV-A16 infections presented with significantly different clinical manifestations. EV-A71 infections frequently lead to severe central nervous system (CNS) complications and even death, while CV-A16 infections often result in milder symptoms that resolve within a few weeks [15]. Nevertheless, over the past years, accumulating evidence has revealed that HFMD in patients infected with CV-A16 can also develop into a serious stage with neurological complications, and the overall condition of these patients and their clinical symptoms are generally consistent with those of severe HFMD patients infected with EV-A71 [16].…”
Section: Introductionmentioning
confidence: 99%